Risk factors associated to Fournier gangrena: Factores de riesgo asociados a gangrena de Fournier - Regalado-Altamirano, Jose C. (2018)
Introducción:Fournier gangrene is a necrotizing fasciitis that affects the perineal, perianal, genital and lower third of the abdomen that leads to necrosis and gangrene of the underlying tissue and compromises in a fulminating and progressive way the life of the patient. It is considered that there are various factors that favor its appearance. The objective of this article is to carry out an in-depth review of risk factors and predisposing conditions of Fournier's gangrene during the last years. Methods: A systematic review of scientific articles, clinical reviews and case reports; both in Spanish and English, related to the subject. The search sources used were: Google Scholar, ScienceDirect - Elsevier library, PubMed, Scielo. For this review, the published articles that had investigative and theoretical-conceptual experiences from 2008 to the present. Results: Based only on 21 of the reviewed articles, it was evidenced that the great majority of patients were male because they were a group of risk, and had an important underlying organic condition; highlighting diabetes mellitus, chronic alcoholism, immunosuppression and other comorbidities. Conclusion: Fournier's gangrene is an entity that can be lethal, which is favored by different risk factors, whose triggering cause is a disease debilitating as well as perirectal or urogenital conditions that have not been treated correctly. Due to its severe prognosis, an early diagnosis with a good management of the risk factors and a Appropriate, early and aggressive multidisciplinary intervention are essential for a good evolution.     DOI 10.25176/RFMH.v18.n4.1736